Myocardial infarction mortality and its association with selected risk factors: prospective study data - D. A. Mamaradzhapova; R. Sh. Mamutov (Кардиоваскулярная терапия и профилактика)
Aim. То study myocardial infarction (MI) mortality and its links with selected risk factors (RFs) in an non-organized population of 40-59-year-old men followed up for 25 years.Material and methods. The baseline examination was performed as a cross-sectional epidemiologic study in a representative sample from Tashkent City male population (1979-80). Up to 2005, during 25 years of the follow-up, mortality certificates of all previously examined 40-59-year-old men were analyzed.Results. Over 25 years, among 1528 40-59-year-old men, examined at baseline, 257 (16,8%) MI deaths were registered. MI deaths accounted for 32,2% and 56,8% of all-cause and cardiovascular disease (CVD) mortality, respectively. During the follow-up period, MI mortality increased from 4,4 to 10,5 deaths per 1000/year. Conclusion. RFs, particularly, hyperlipidemia, arterial hypertension and smoking, were associated with higher risk of MI death. Increased number of RFs was linked with higher risk, especially for 4 RFs or more.